Pintando com as mãos : uma experiência poético- -pedagógica na formação de professores de arte - Pellegrin, Ricardo de (2019)
This paper presents some considerations on a poetic-pedagogical activity named Finger painting, which was carried out among undergraduate students from the Teaching Degree in Visual Arts - PARFOR from Unochapecó. The theoretical framework adopted for the study is draw on the insights provided by a/r/tography. The main goal is to comprehend the performance of professor-artist in higher education. The findings reveal that experiences from Relational Art contribute to the professional development of Art teachers